Marriage, economy, and freedom : the marriage plot in the works of women writers in the tanzimat period = Evlilik, ekonomi, özgürlük : tanzimat dönemi kadın yazarların eserlerinde evlilik olay örgüsü - Topkara, Sümeyya. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in Social Sciences, 2023., 2023)
This thesis discussed how the marriage plot in the works of Ottoman women writers reflects the position of modern and educated women within the traditional marriage and family codes. This discussion focused on five books; four from women writers: Fatma Aliye’s Levayih-i Hayat, Fatma Fahrünnisa’s Dilharap, two stories named “Tashih” and “Hüsn-ü Muamele” from Makbule Leman’s collected works Makes-i Hayal, and Fatma Şadiye’s storybook Hikayat-ı Nuşin. The fifth book, Ahmet Mithat Efendi’s Felsefe-i Zenan, discussed as the pioneer example of the representation of modern and educated woman’s situation in traditional marriages and read together with Levayih-i Hayat, which was similarly written in epistolary form. In these novels and stories, Ottoman women writers discussed many different problems including women’s education, economic independence, forced arranged marriages, restriction of a married woman’s freedom, and the dilemmas of Islamic divorce law. This thesis primarily focused on how women writers constructed these problems within the marriage plot, which was restricted by the Ottoman sharia law’s regulations. While these regulations limited the horizons of plot by not allowing the creation of standard romance characters or love marriages; it also allowed women writers to create unique marriage plots that goes beyond the happy ending to represent the inequality between sexes in marriage. It is argued that through marriage plot writers represented an ideal of educated woman and modern family which are directly related to the women’s economic independence.
Keywords: Turkish literature -- Women writers -- History and criticism.; Turkey -- History -- Tanzimat, 1839-1876 -- Fiction.